Diagnostic performance and characteristics of anterior nasal collection for the SARS-CoV-2 antigen test: a prospective study - Yuto Takeuchi (Nature Portfolio, 2021)
Abstract The clinical utility of antigen test using anterior nasal samples has not been well evaluated. We conducted a prospective study in a drive-through testing site located at a PCR center to evaluate the diagnostic performance of the antigen test QuickNavi-COVID19 Ag using anterior nasal samples and to compare the degrees of coughs or sneezes induction and the severity of pain between anterior nasal collection and nasopharyngeal collection. The study included a total of 862 participants, of which 91.6% were symptomatic. The median duration from symptom onset to sample collection was 2.0 days. Fifty-one participants tested positive for severe acute respiratory syndrome coronavirus 2 on reverse transcription PCR (RT-PCR) with nasopharyngeal samples, and all of them were symptomatic. In comparison to the findings of RT-PCR, the antigen test using anterior nasal samples showed 72.5% sensitivity (95% confidence interval [CI] 58.3–84.1%) and 100% specificity (95% CI 99.3–100%). Anterior nasal collection was associated with a significantly lower degree of coughs or sneezes induction and the severity of pain in comparison to nasopharyngeal collection (p < 0.001). The antigen test using anterior nasal samples showed moderate sensitivity in symptomatic patients who were at the early stages of the disease course but was less painful and induced fewer coughs or sneezes.